MULTI-OBJECTIVE OPTIMIZATION MODEL FOR BIOENERGY SUPPLY CHAIN DISTRIBUTION - Krisnaningsih, Erni; Dwiyatno, Saleh; Cahyadi, Dadi; Rasjidin, Roesfiansjah (Jurnal Teknologi Industri Pertanian, 2025)
Determining optimal distribution routes in managing efficient transportation distances is a challenge in the bioenergy supply chain. Adequate distribution arrangements can improve distribution in the bioenergy supply chain. Optimizing distribution arrangements can help reduce transportation costs, avoid delays, and improve distribution efficiency. The optimal distribution strategy must consider choosing routes that minimize distribution distances from agricultural centres to power plants. This study aimed to determine the location of collection points and optimal distribution routes in the distribution of the bioenergy supply chain. Centre of gravity (COG) method for locating collection centres. Determination of optimal distribution routes with a combination of ME-MCDM and spatial Dijkstra approaches. The results showed that the centre point at -60.53'42.6" S and 105.035'70.8" E is the biomass collection area for suitable bioenergy. Our proposed method of spatial combination of Dijkstra and multicriteria decision making (ME-MCDM) based on Expert considerations on a more logical bioenergy optimal distribution solution, taking into account sustainability, has TAV 1700,74 with P (V1, V5) = (V1, V2, V4, V5). Managerial Implications for Bioenergy-Producing Companies and Policy Stakeholders From operational efficiency to reducing carbon emissions, this model can help companies better manage their bioenergy distribution and contribute to business sustainability. Keywords: bioenergy distribution, Centre of Gravity (COG), model optimisation, ME-MCDM Spatial Dijkstra